Remote sensing in soil erosion assessment for land resources management - Prasad, Jagdish; Srivastava, Rajeev; Nagaraju, M S S; Ingale, Sagar N (Indian Farming, 2020)
Soil erosion assessment and monitoring is important for sustainable management of land resources. Remote sensing and GIS provide near real-time data of the land resources and helps in quick assessment of land resources for taking appropriate measures for its optimum management.